Study of incidence of central line associated blood stream infections in patients admitted in intensive care unit - Dubey, Prachi; Varma, Sanjay; Kujur, Anupam; Sharma, Bhuwan (International Journal of Advances in Medicine, 2021)
Background: Central venous catheterization is a relatively common procedure in many branches of medicine particularly in anaesthesia and intensive care medicine. Central venous catheters give an easy access for giving drugs as well as for sampling of blood, but they can also be a cause of blood stream infection and sepsis. Methods: Patients who requiring central venous catheter were selected, relevant blood investigations were done before insertion of catheter and after 48 hours after insertion. With the suspicion of new infection, physical examination and laboratory work-ups were carried out to identify the other source of infection. Results: Total 96 patients were selected with mean age of 40.0±13.89 years. The incidence of central line-associated bloodstream infection/catheter-related bloodstream infection (CLABSI/CRBSI) in our hospital based study in intensive care units comes out 34.37%. The CLABSI/CRBSI patients (n=33) on general physical examination 5 patients have bradycardia, hypertension hypothermia oliguria altered mental status hypotension tachypnea tachycardia and 26 patients have developed fever during the course of illness. The predominant organism isolated in CLABSI/CRBSI patients is Staphylococcus aureus. Central venous catheters are useful in getting access and also source of blood stream investigation. Site of catheter, duration of catheter and co morbidities acts as risk factor for infection. Conclusions: By knowing the risk factors to cause catheter related infections, risk of getting infection can be lowered by using aseptic technique during insertion and proper catheter care and this can further reduces morbidity and mortality related to central venous catheters.